ANALISIS PENATAUSAHAAN BARANG MILIK NEGARA (BMN) DI LINGKUNGAN KEMENTERIAN AGAMA KABUPATEN DONGGALA - Setiadi, Ivan (Katalogis, 2018)
The study aims are to describe the process of administration of State Property (BMN) in the Ministry of Religious Affairs of Donggala Regency and to offer a solution in the perspective of the basic concept of accounting. The study applies qualitative method, with the post-positivism approach. The process of collecting data is done through observation, interview, and document analysis using triangulation model technique. The results of the study show (1) the recording is based on the application but it is not effective in use, (2) the recording is not supported by the specification of goods documents, (3) the updating of BMN asset data and information are not performed, (4) the inventory of BMN assets never performed, (5) BMN report not equipped with notes on reports of state property (CalBMN). Alternative of administration of BMN in the perspective of the basic concept of accounting is the entity theory, such as: (1) it needs real policy related to the use of the application as needed, (2) collecting initial information on the asset completely, (3) it needs policy related to controlling regularly (4) the substance of presentation is not only in formal reports, (5) the complete report is the suitability of documents, physical assets and records in the book of inventory. The good mechanism of administration of BMN, then the process of transparency and accountability in the management of BMN will be realized.